Failures of deep excavation in soils - Cheung, Kar Wah. (2008)
Case records of deep excavation failures in soils are emphasized in this document. They are classified into three groups according to their shoring systems: failures associated with tied-back or anchored walls, strutted or braced walls, and cantilevered unbraced walls.